2011
DOI: 10.5194/acp-11-12453-2011
|View full text |Cite
|
Sign up to set email alerts
|

Sources of carbonaceous aerosols and deposited black carbon in the Arctic in winter-spring: implications for radiative forcing

Abstract: Abstract. We use a global chemical transport model (GEOSChem CTM) to interpret observations of black carbon (BC) and organic aerosol (OA) from the NASA ARCTAS aircraft campaign over the North American Arctic in April 2008, as well as longer-term records in surface air and in snow (2007)(2008)(2009). BC emission inventories for North America, Europe, and Asia in the model are tested by comparison with surface air observations over these source regions. Russian open fires were the dominant source of OA in the Ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
333
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(370 citation statements)
references
References 109 publications
(168 reference statements)
30
333
3
4
Order By: Relevance
“…The 50 % higher BC emissions over 40 • -70 • N translates to a 50 % higher BC burden and 70 % higher BC surface mixing ratio north of 50 • N. There is also a similar impact of higher SO 2 emissions over 40 • -70 • N on Arctic sulphate mixing ratios. This confirms the important role of aerosol and precursor sources in mid-and high latitudes in affecting Arctic aerosol abundance, and suggests that current emissions are likely underestimated, as also shown by Wang et al (2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The 50 % higher BC emissions over 40 • -70 • N translates to a 50 % higher BC burden and 70 % higher BC surface mixing ratio north of 50 • N. There is also a similar impact of higher SO 2 emissions over 40 • -70 • N on Arctic sulphate mixing ratios. This confirms the important role of aerosol and precursor sources in mid-and high latitudes in affecting Arctic aerosol abundance, and suggests that current emissions are likely underestimated, as also shown by Wang et al (2011).…”
Section: Discussionsupporting
confidence: 65%
“…This effect depends on the location of absorbing aerosols in relation to the cloud layer (e.g., McFarquhar and Wang, 2006;Koch and Del Genio, 2010). Absorbing aerosols deposited onto snow and ice surface can enhance absorption of shortwave radiation at the surface, resulting in a warming of the lower atmosphere and more-rapid melting of snow and ice (Warren and Wiscombe, 1980;Flanner et al, 2007;Doherty et al, 2010;Qian et al, 2011;Wang et al, 2011). Therefore, global three-dimensional aerosol distributions, particularly over remote regions away from sources (e.g., the Arctic and upper troposphere), are important in the Earth's climate system.…”
Section: Introductionmentioning
confidence: 99%
“…The model framework includes gas-aerosol partitioning of semi-volatile organic compounds (Liao et al, 2007;Henze et al, 2007Henze et al, , 2009Fu et al, 2008;Heald et al, 2011;Wang et al, 2011), and heterogeneous chemistry (Jacob, 2000). Coupling between gas-phase chemistry and sulfateammonium-nitrate aerosol is described by Park et al (2004) and Pye et al (2009).…”
Section: Global Modelmentioning
confidence: 99%
“…The relative abundance of Arctic aerosol data has facilitated extensive research on particulate sources (e.g., Sirois and Barrie, 1999;Stohl et al, 2013;Nguyen et al, 2013;Yttri et al, 2014). Fewer studies have identified the sources of snow impurities, which represent the deposited and surface albedoinfluencing portion of the aerosol, and often these studies are reliant on modelled snow concentrations (e.g., Skeie et al, 2011;Wang et al, 2011) rather than measurements (e.g., Hegg et al, 2009Hegg et al, , 2010. Also, variability has been seen across existing snow apportionment studies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, variability has been seen across existing snow apportionment studies. For example, previous studies show significant disagreement in the apportionment of BC during the Arctic winter, ranging from approximately 10 to over 90 % attributed to biomass burning (e.g., Wang et al, 2011 ande.g., Hegg et al, 2009, respectively). To the best of the authors' knowledge, no quantitative source apportionment has previously been conducted using temporally refined fresh Arctic snow samples.…”
Section: Introductionmentioning
confidence: 99%